Clinical and laboratory features of childhood-onset primary Sjögren's syndrome: A retrospective study from China - Liu, Chenxi; Jin, Yingying; Huang, Hua; Ding, Fei; Xu, Xuemei; Bao, Shengfang; Yang, Zhen; Jin, Yanliang (Frontiers in Pediatrics, 2023)
Abstract Introduction: The initial presentations of childhood-onset primary Sjögren’s syndrome (C-pSS) are varied, which makes the diagnosis challenging. This study aimed to improve the diagnosis and evaluation of C-pSS by summarizing the clinical and laboratory features. Methods: 49 patients with childhood-onset pSS between July 2015 and August 2022 in the Department of Rheumatology and Immunology of Shanghai Children’s Medical Centre were enrolled. The clinical manifestations and laboratory examinations of these patients were compared based on presence or absence of thrombocytopenia, parotitis, and whether the immunological markers including ANA, RF, SSA/Ro52, SSA/Ro60, and SSB is positive. Results: The mean age of pSS diagnosis was 10.34±3.45 years old and the ratio of boys and girls was 1:6. In thrombocytopenia group, parotitis (P=0.037), organ involvement except hematology (P=0.002), positive SSB (P=0.004), and positive RF (P=0.001) were less frequently observed; the level of complement C4 (P=0.038) and white blood cells (P=0.002) dropped and increased significantly, respectively. SSB (P=0.010) and RF (P=0.004) were the independent potential protective factors thrombocytopenia in pSS. In parotitis group, higher ANA titer (P=0.028), higher focus score of labial gland biopsy (P=0.001), positive RF (P=0.005), positive SSA/Ro52 (P=0.038), positive SSA/Ro60 (P=0.002), and positive SSB (P=0.001) were more frequently observed. Higher ANA titer (P=0.093) and positive RF (P=0.098) were the non-independent risk factors of parotitis in pSS, and positive SSB (P=0.039) was the independent risk factors of parotitis in pSS. The value of haemoglobin was significantly lower in patients with positive SSA/Ro52 and positive SSA/Ro60 (P=0.022, and P=0.029, respectively), while the level of immunoglobulin G was significantly higher in patients with the same group (P=0.048, and P=0.007, respectively). Conclusions: Positive SSB and positive RF maybe the independent potential protective factors of thrombocytopenia in pSS. In contrast, higher ANA titer and positive RF were the non-independent risk factors of parotitis in pSS, and positive SSB was the independent risk factors of parotitis in pSS. In the future, more studies are needed to reveal a diagnostic role and pathogenic mechanism of immunological markers in C-pSS. Key words: childhood-onset, primary Sjögren’s syndrome, clinical manifestation, laboratory examination, immunological markers